Pelatihan Penggunaan Learning Management System (LMS) Bagi Dosen FKIP Universitas Cenderawasih - Irwandi Yogo Suaka; Rio Wakhid Hujjatul Islam; Suriyah Satar; Nurbaya Satar; Hanida Listiani; Agnes Teresa Panjaitan (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2023)
ABSTRACT The use of technology in education has become an unavoidable necessity in this digital era. This article discusses the implementation of training for lecturers at the Faculty of Teacher Training and Education (FKIP) Cenderawasih University in implementing the Learning Management System (LMS), an online platform that is able to increase the efficiency of teaching and learning at the tertiary level. This training aims to improve lecturers understanding and skills in using LMS as a means to manage learning material, present material interactively, and facilitate communication between lecturers and students. Training methods include practical training sessions, case studies, and group discussions. Training findings showed a significant increase in lecturers understanding and skills regarding LMS use. Lecturers are able to seamlessly manage their courses, present material more interactively, and take advantage of the collaborative features of the LMS. These resultas provide a positive picture of the potential of LMS in improving the quality of teaching at FKIP Cenderawasih University. Keywords: Learning Management System (LMS), Training, Lecturers